Does financial development boost entrepreneurship? Evidence from transitory economies - Ul-Haq, Jabbar; Sattor, Asrorzoda Ubaidullo; Hye, Qazi Muhammad Adnan; Justin, Lekini Dieudonne; Visas, Hubert (Asian Journal of Economic Modelling, 2025)
The transition from planned to market-oriented economies presents a unique landscape for the study of entrepreneurship. Entrepreneurship is crucial to reducing unemployment, mitigating poverty, and promoting economic growth across the world, especially in the economies of the global South. Some people opine that not having enough money is a big reason why more people don't start their own businesses. On the other hand, a well-developed financial system with strong financial institutions and markets can help people start their own businesses, which is good for the country's economy. This study analyzes the liaison between financial developments and entrepreneurship in these transitioning countries. The empirical analysis uses the panel fixed effects, Driscoll and Kraay standard errors (DKSEs), feasible generalized least-squares (FGLS), and panel-corrected standard errors (PCSEs) models. The results reveal an inverted U-shaped relationship between financial development and entrepreneurship in the transitory economies. We also use sub-indices of financial development and find similar results. The relationship between financial institutions and entrepreneurship is an inverted U shape. The relationship between financial markets (FM) and entrepreneurship yields similar but insignificant results. The role of foreign direct investment (FDI) and technological innovations is positive in promoting entrepreneurial activities in these economies. The findings of the study will help the governments and policymakers of these countries to devise such policies as are required, as they reduce the financial constraints and boost entrepreneurial activity that leads to economic decolonization.